How can we measure bladder volumes in women with advanced pelvic organ prolapse?. (August 2015) - Cassadó, J.; Espuña‐Pons, M.; Díaz‐Cuervo, H.; Rebollo, P.; on behalf of the GISPEM Group
ABSTRACT Objectives To compare bladder volumes determined by three different formulae using measurements obtained from two‐dimensional translabial ultrasound (2D‐US), with true bladder volumes, in women with advanced pelvic organ prolapse (POP). Methods This was a prospective observational multicenter study of consecutive women on the waiting list for prolapse surgery in 24 gynecology departments. All women had a symptomatic genital prolapse Stage 2 or higher according to the Pelvic Organ Prolapse Quantification System (POP‐Q). Bladder volumes were calculated before and after spontaneous voiding by 2D‐US, and true bladder volumes were determined by micturition and catheterization. Volumes determined by US were calculated using three formulae (Haylen, Dietz and Dicuio). Correlation was calculated between the volume determined by US measurement before micturition and the true volume, and also between the volume determined by US measurements after micturition and the true volume. Correlations (Spearman's rho) and concordance (intraclass correlation coefficient (ICC)) were estimated for each of the three formulae considered. Results One‐hundred and eighty‐six women with POP were included in the study. A total of 349 bladder volumes (186 before micturition and 163 after micturition) were obtained. Good correlation (rho, 0.818–0.849) and concordance (ICC, 0.827–0.898) were found between total measured volume (volume of spontaneous bladder voiding + volume obtained from catheterization) and the volume determined by US using the three different formulae, as well as between the post‐void residual volume measured by catheterization and the post‐void volume calculated by US using the three formulae (rho, 0.739–0.777; ICC, 0.840–0.877). Conclusions Bladder volumes in women with advanced POP can be measured easily by 2D‐US. Volumes determined using the three different formulae show good correlations and concordance with true bladder volume. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.